Teaching performance and learning achievements in university students (Revista Innova Educación, 2021)
The objective was to determine the relationship of teaching performance with the achievement of learning in the Design Workshop subject of the Architecture career at the César Vallejo University Chimbote campus, 2020, from the students' perspective. Therefore, the research had a quantitative, descriptive correlational approach of non-experimental design. For the sample, 35 students were considered to whom a questionnaire with five response alternatives with 39 items was applied to measure the two variables: teaching performance (four dimensions) and learning achievement (three dimensions). Spearman's correlation analysis showed a p-value of 0.031 and an r-value of 0.364, so both variables have a low-level positive relationship. This means that there will be better learning achievement when the teaching performance is better. It is concluded that teaching performance has a significant relationship with the achievement of learning.
Keywords: performance; teaching performance; achievement; teacher evaluation